Analisis Hubungan Pengajaran dengan Mutu Pelayanan Rumah Sakit di Rumah Sakit Islam Kota Padang - M Adharudin; Yulastri Arif; Dorisnita Dorisnita (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Hospital service quality is an assessment of services obtained from patients with cost-efficient and results from the organization's organizational performance. Free market competition requires us to improve quality in all fields, especially in health services to be recognized internationally, the phenomenon of people prefering to seek treatment abroad is a big challenge in improving the quality of hospital services. The purpose of this study was to determine the relationship of Teaching with the services quality in Padang City Islamic hospitals. The study design used was descriptive correlation with cross sectional design. The sample of this study were 325 inpatients. The results of this study prove that there is a relationship between teaching and service quality in Padang City Islamic hospitals (P = 0.006). This study recommends hospitals to increase the active role of nurses in improving service quality with the COPA model approach, which is teaching that can be applied in hospitals.